Teaching Approaches and Methodologies : A Review of Post COVID-19 - Vimala, Govindaraju; Zuraini, Seruji; Yeng, Sin Kit (Hong Kong Journal of Social Sciences, 2023)
The COVID-19 pandemic is shining a severe light on the exposures and challenges faced by humans. The pandemic transformed education systems around the world, causing the greatest disruption to the education system, especially teaching and learning more specifically in the approaches and methodologies. The COVID-19 pandemic created movement restrictions and social distancing measures, besides this situation leading to a severe impact on traditional educational practices. This article aims to explore a literature review of the educational system that has been forced to adjust its approaches and methods to e-learning in line with the era of COVID-19. Methodology: This article focuses on the theoretical aspects of the COVID-19 pandemic, which poses significant challenges to education worldwide, forcing a major shift away from learning and teaching face to face interactive environments. It is presented in five mutually inclusive sections as follows; (a) Teaching Approaches and Methodologies During Pandemic; (b) Adaptations of Post COVID-19 Online Teaching and Learning: Methods and Approaches in Higher Education; (c) Challenges On Post-COVID-19 Online Teaching and Learning Method and Approaches; (d) Strategies to overcome the Challenges on post-covid-19 online teaching and learning method and approaches and (e) Theory of Transactional Distance in Post COVID-19 Online Teaching and Learning Method and Approaches. The COVID-19 pandemic has forced many educational institutions to adapt their teaching approaches and methodologies to remote and hybrid learning models. In the post-COVID-19 era, these new teaching approaches and methodologies may continue to be applied and refined to improve student learning outcomes. The key to promoting novelty and originality in teaching approaches and methodologies post-COVID-19 is to prioritize flexibility, creativity, and student-centered learning. By empowering students to take ownership of their learning and encouraging them to be innovative and creative, educators can help prepare them for a rapidly changing and unpredictable world.